PENGARUH GENDER TERHADAP GAYA BELAJAR SISWA DI SDN 35 GEDONG TATAAN KABUPATEN PESAWARAN TAHUN PELAJARAN 2017/2018 - EVA, NUR; PUTRI, RACHMAWATI (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research aims to know the influence of gender towards the students learning styles at SDN 35 Gedong Tataan Academic Year 2017/2018. This research also to know about the tendency of learning styles and a combination of learning styles. The method used in this research is quantitative descriptive. The selected samples were class III and V consist of 33 students, with purposive sampling technique. The data were collected by questionnaire and documentation. Data collection technique are using observation, interviews, and questionnaire of learning styles. Then, data were analyzed using chi-square test statistic. The results showed that there is influence of gender towards the students learning styles. Based on the results of chi-square test using SPSS 23 for windows program shows the effect of gender on students learning style with Chi-Square value = 6,912>5,991 and significance value that is 0,032<0,05